PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT INTERTEKNO GRAFIKA SEJATI-JAKARTA SELATAN - Laelatun Hamdiyah; Aden Prawiro Sudarso (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. The purpose of this study is to determine the effect of motivation and work environment on employee performance at PT Intertekno Grafika Sejati - South Jakarta, both partially and simultaneously. The research method used is a quantitative method with a descriptive and associative approach. The sampling technique uses saturated samples obtained by a sample of 60 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. Work motivation and work environment have a significant effect on employee performance with the regression equation value Y = 4.355 + 0.526X1 + 0.359X2. The correlation coefficient value or level of influence between the independent variable and the dependent variable is obtained at 0.760, which means that the Work Motivation (X1) and Work Environment (X2) variables have a very strong relationship with Employee Performance (Y). The determination coefficient value is 0.779 or 77.9% while the remaining 22.1% is influenced by other factors. Hypothesis test F count value > F table or (40.387 > 2.761). This is further supported by a p-value < signiﬁcant 0.05 (0.000 < 0.05). Therefore, H0 is rejected and H3 is accepted, indicating a significant simultaneous effect between work motivation and work environment on employee performance at PT Intertekno Grafika Sejati – South Jakarta. Keywords: Work Motivation, Work Environment, Employee Performance